Long-Term Natural Outcomes of Simple Hemorrhage Associated with Lacquer Crack in High Myopia: A Risk Factor for Myopic CNV? - Bing Liu; Xiongze Zhang; Lan Mi; Ling Chen; Feng Wen (Journal of Ophthalmology)
Purpose. To investigate the relationship between simple hemorrhage (SH) associated with lacquer crack (LC) and myopic choroidal neovascularization (CNV) in high myopia. Methods. A cross-sectional evaluation including best-corrected visual acuity (BCVA), axial length, refractive error, color fundus photography, and spectral domain optical coherence tomography (SD-OCT) was performed in patients diagnosed with high myopia and SH. Fundus fluorescein angiography and indocyanine green angiography were performed if the eye was suspected with CNV. Results. Thirty-three eyes of 27 patients with SH were enrolled in the study. None of the eyes developed CNV at final examination following the occurrence of hemorrhage. Recurrent hemorrhage was observed in 36.5% of the eyes. Compared with the initial BCVA, the final BCVA was significantly improved (P<0.001) and correlated with the integrity of the ellipsoid zone in SD-OCT. There was no significant difference in the final BCVA between group 1 (LC crossed the central fovea) and group 2 (no LC crossed the central fovea) (P=0.299). Conclusions. SH associated with LC is not a risk factor for the development of myopic CNV in patients with high myopia. LCs have little influence on the final BCVA unless the integrity of the ellipsoid zone in the central fovea is disrupted.